2011
DOI: 10.1007/s10570-011-9637-5
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of lysozyme-cellulose amide-linked conjugates on cellulose I and II cotton nanocrystalline preparations

Abstract: Lysozyme was attached through an amide linkage between some of the protein's aspartate and glutamate residues to amino-glycine-cellulose, which was prepared by esterification of glycine to preparations of cotton nanocrystals. The nanocrystalline preparations were produced through acid hydrolysis and mechanical breakage of the cotton fibers from a scoured and bleached cotton fabric and a scoured and bleached, mercerized fabric, which was shown to produce cellulose I (NCI) and cellulose II (NCII) crystals respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 37 publications
(40 reference statements)
1
35
0
Order By: Relevance
“…108 The nal DS was reported as 0.029, indicating 90% complexation of the surface graed terpyridine with ruthenium. 108 Esterication was used as a precursor to further modica-tion in the attachment of lysozyme to cellulose nanocrystals by Edwards et al 86 Cellulose nanocrystals were rst modied with Fmoc-glycine using DIC as a coupling agent, before deprotection and attachment of lysozyme by amidation. 86 The level of modication was reported as DS ¼ 0.09 for the esterication, but lateral dimensions for the nanocrystals are not given in the paper making conversion of this value into DS problematic.…”
Section: Further Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…108 The nal DS was reported as 0.029, indicating 90% complexation of the surface graed terpyridine with ruthenium. 108 Esterication was used as a precursor to further modica-tion in the attachment of lysozyme to cellulose nanocrystals by Edwards et al 86 Cellulose nanocrystals were rst modied with Fmoc-glycine using DIC as a coupling agent, before deprotection and attachment of lysozyme by amidation. 86 The level of modication was reported as DS ¼ 0.09 for the esterication, but lateral dimensions for the nanocrystals are not given in the paper making conversion of this value into DS problematic.…”
Section: Further Modificationsmentioning
confidence: 99%
“…The lysozyme attachment is then analysed by use of a "nitrogen to protein conversion factor" rather than direct measurement of the nitrogen concentration in the lysozyme starting material leading to gures that cannot be directly related to DS. 86 Amidation was used as a precursor to the popular azidealkyne cycloaddition reaction. Filpponen et al used EDC to attach both azide and alkyne functionalities to oxidized cellulose nanocrystals.…”
Section: Further Modificationsmentioning
confidence: 99%
“…Enzymes can be formulated with nanocellulose as covalent linkages, salt bridges, and with physical inclusion complexes [13][14][15][16][17][18][19][20][21]. The hydrophilic surface properties provide a biocompatible matrix for selective activity to occur.…”
Section: Biosensors With Polymer Biopolymer and Enzyme Composites Ofmentioning
confidence: 99%
“…Edwards et al reported very high lysozyme activity when the hydrolase was attached to cotton cellulose nanocrystals [18], which suggests the activity of anti-microbial enzymes can be bolstered when immobilized on cotton cellulose nanocrystals, and this approach may have further implications for use to detect as well as inhibit formation of microbial biofilms [19]. Finally it is noteworthy that cellulases have been used in an approach that demonstrates how enzymatic digestion of cellulose in combination with soft lithography can be used to obtain patterned surfaces [20].…”
Section: Biosensors With Polymer Biopolymer and Enzyme Composites Ofmentioning
confidence: 99%
“…NCC is generally prepared by acid-catalyzed hydrolysis of cellulose 5 , and has drawn increasing attention due to its excellent physicochemical properties (including high surface-to volume ratios, high aspect ratios, high stiffness, 3 good strength) and sustainability 6 . Glucose oxidase 7 , peroxidase 8 , and lysozyme 9 , as well as papain 10 were successfully immobilized onto NCC with enhanced activity, stability and catalytic efficiency. This indicated that the novel NCC-based enzyme carriers show great potential and are worthy of further study.…”
Section: Introductionmentioning
confidence: 99%